Development of information dissemination methods that contribute to improving maternal and child healthcare using social networking sites: a community-based cross-sectional study in Japan - Sayaka Ikeda; Yutaka Ueda; Asami Yagi; Mariko Taniguchi; Satoko Matsuzaki; Tsuyoshi Takiuchi; Ai Miyoshi; Hitomi Arahori; Kei Hirai; Tadashi Kimura (BMC, 2022)
Abstract Background In recent years, feelings of isolation among mothers caring for small children has become a significant social issue in Japan. The purpose of this study is to develop a message to alleviate their loneliness, to evaluate the impact of social networking sites (SNS) for delivering such messages, and to propose means of more effective information transmission to promote health for mothers raising small children. Methods Our study was conducted in two stages, first an interview and then a cross-sectional study of the mothers involving a questionnaire survey. The interview was targeted two public-health nurses caring for mothers. Based on these interviews, we developed six messages intended to alleviate the mothers' sense of loneliness, which were vetted by seven mothers. The second stage was to conduct a questionnaire survey of mothers both before and after our selected message as advertisement on Instagram and analyzed the effect. The surveys were collected during routine child health check-ups in the City of Takatsuki, Japan. Results From the six draft messages created based on interviews with public health nurses, we selected the message that most relieves the feeling of loneliness of the mothers who are raising small children. The survey questionnaire was taken by 494 mothers prior to our posting of Instagram advertisements (ads), and afterwards by 419 mothers. The percentage of mothers feeling loneliness tended to decrease after reading the messages (before ads.:8.1%, after ads.:5.8%). 8.6% of the mothers (36/419) remembered seeing the Instagram ads. Mothers with financial anxiety were significantly more likely to have remembered seeing the Instagram ads (p < 0.01). Conclusions Our results indicate that usefulness of SNS messaging for mothers raising small children may reduce their feeling of loneliness. Among the SNS, disseminating child-rearing information on Instagram may be more effective for people with financial instability.